Automatic Identification of Casting Part Numbers based on Machine Vision - Ge, Jinqi (International Journal of Mechanical and Electrical Engineering, 2025)
For the casting of the workpiece number characters are small, and the blade surface reflection, the target and the background of the contrast is low, resulting in the human eye recognition difficulties, low efficiency and other issues. In this paper, a machine vision-based casting workpiece number automatic identification system is designed. First of all, through the high-resolution industrial camera to obtain the image to be recognized, and to be recognized image preprocessing; and then according to the target area characteristics to determine the region of interest, extract the character features to establish a character library; and finally the application of character templates in the character library to achieve automatic recognition of characters in the image to be measured. After the actual test shows that the system can meet the casting workpiece number automatic identification needs, and stable performance, has good practicality and feasibility, thus proposed to improve the identification system. Whether in the generation of the manufacturing process, or testing and maintenance process, need to be organized according to the workpiece number, workpiece number is equivalent to each casting ID, can be convenient to record and query the casting in the generation of the manufacturing process of the relevant information as well as testing and maintenance of defects found in the process of information.